Mutational changes in S-cone opsin genes common to both nocturnal and cathemeral Aotus monkeys - Levenson, David H. (2007)
Aotus is a platyrrhine primate that has been classically considered to be nocturnal. Earlier research revealed that this animal lacks a color vision capacity because, unlike all other platyrrhine monkeys, Aotus has a defect in the opsin gene that is required to produce short‐wavelength sensitive (S) cone photopigment. Consequently, Aotus retains only a single type of cone photopigment. Other mammals have since been found to show similar losses and it has often been speculated that such change is in some fashion tied to nocturnality. Although most species of Aotus are indeed nocturnal, recent observations show that Aotus azarai, an owl monkey species native to portions of Argentina and Paraguay, displays a cathemeral activity pattern being active during daylight hours as frequently as during nighttime hours. We have sequenced portions of the S‐cone opsin gene in A. azarai and Aotus nancymaae, the latter a typically nocturnal species. The S‐cone opsin genes in both species contain the same fatal defects earlier detected for Aotus trivirgatus. On the basis of the phylogenetic relationships of these three species these results imply that Aotus must have lost a capacity for color vision early in its history and they also suggest that the absence of color vision is not compulsively linked to a nocturnal lifestyle.